"LONG COVID"—A hypothesis for understanding the biological basis and pharmacological treatment strategy. Issue 1 (13th January 2022) - Jarrott, Bevyn; Head, Richard; Pringle, Kirsty G.; Lumbers, Eugenie R.; Martin, Jennifer H.
Abstract: Infection of humans with SARS‐CoV‐2 virus causes a disease known colloquially as "COVID‐19" with symptoms ranging from asymptomatic to severe pneumonia. Initial pathology is due to the virus binding to the ACE‐2 protein on endothelial cells lining blood vessels and entering these cells in order to replicate. Viral replication causes oxidative stress due to elevated levels of reactive oxygen species. Many (~60%) of the infected people appear to have eliminated the virus from their body after 28 days and resume normal activity. However, a significant proportion (~40%) experience a variety of symptoms (loss of smell and/or taste, fatigue, cough, aching pain, "brain fog, " insomnia, shortness of breath, and tachycardia) after 12 weeks and are diagnosed with a syndrome named "LONG COVID." Longitudinal clinical studies in a group of subjects who were infected with SARS‐CoV‐2 have been compared to a non‐infected matched group of subjects. A cohort of infected subjects can be identified by a battery of cytokine markers to have persistent, low level grade of inflammation and often self‐report two or more troubling symptoms. There is no drug that will relieve their symptoms effectively. It is hypothesized that drugs that activate the intracellular transcription factor, nuclear factor erythroid‐derived 2‐like 2 (NRF2) may increase the expression of enzymes to synthesize the intracellular antioxidant, glutathione that will quench free radicals causing oxidative stress. The hormone melatonin has been identified as an activator of NRF2 and a relatively safe chemical for most people to ingest chronically. Thus, it is an option for consideration of re‐purposing studies in "LONG COVID" subjects experiencing insomnia, depression, fatigue, and "brain fog" but not tachycardia. Appropriately designed clinical trials are required to evaluate melatonin. Abstract : It is accepted that SARS‐CoV‐2 virus is transmitted in the air by exhaled droplets from infected people and if inhaled by a close contact, it binds to endothelial cells of blood vessels in the naso‐pharnygeal tract where it rapidly replicates. This causes oxidative stress due to formation of free radicals that inhibits the normal synthesis of cytoprotective enzymes and proteins resulting in prolonged depletion of the intracellular antioxidant, glutathione which could be a cause of "LONG COVID". It is hypothesized that elevation in the levels of the key transcription factor NRF2 by the hormone, melatonin will restore enzymes that synthesize glutathione.